Perineal Wound Identification With Maternity Cool Gel Pad (MCGP) Care Interventions - Bina Melvia Girsang; Eqlima Elfira; Farida Linda Sari Siregar (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Postpartum mothers with an indication of episiotomy will experience a higher level of pain. This birth canal trauma is acute and is expected to recover in a short period of time, can be measured, and without serious complications. The aim of this study was to identify the healing process of postpartum maternal perineal wounds. The intervention was carried out on 31 postpartum mothers with the selection using purposive sampling technique. Maternity cool gel pad (MCGP) which was applied to the perineal wound care intervention on the 2nd and 3rd day after delivery showed the wound healing process was observed using the REEDA measuring instrument and analyzed using the T one sample test. The repair of the wound repair scale from the mean REEDA score (10.81 ± 2.98) occurred in all wounds of the study respondents at post intervention (5.32 ± 1.73). Maternity cool gel pad intervention assisted the wound healing process in post intervention data (P <0.005). The results of this study can be indicative of an inflammatory response locally in perineal wounds, but further research is needed to observe the impact of perineal wound healing with a combination of methods that can help evaluate the perineal wound repair process that can be done by mothers independently at home.